2019
DOI: 10.22456/1679-9216.89668
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration, Antimicrobial Resistance and Typing of Salmonella enterica: Profile of Strains Carried in the Intestinal Contents of Pigs at Slaughter in Southern Brazil

Abstract: Background: Despite a strong association between Salmonella isolation and slaughter hygiene, as measured by the Enterobacteriaceae levels on pre-chill carcass surfaces, a high variation in this association was observed between sampling days within the same slaughterhouse. It was hypothesised that in a scenario of high exposure on the farm, batches with a high prevalence of carrier pigs shedding a high number of Salmonella may enhance the risk of contamination on some slaughter days. Thus, the aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
(48 reference statements)
1
9
0
Order By: Relevance
“…in pig carcasses in slaughterhouses that use traditional inspection systems [ 29 , 50 , 51 , 52 , 53 , 54 ]. Paim et al [ 55 ] detected an 8% frequency of Salmonella spp. in a slaughterhouse in southern Brazil, while Kich et al [ 56 ] reported a frequency of 24%, Cê [ 57 ] 1.11%, and Corbellini et al [ 33 ] 11.5% in the same region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in pig carcasses in slaughterhouses that use traditional inspection systems [ 29 , 50 , 51 , 52 , 53 , 54 ]. Paim et al [ 55 ] detected an 8% frequency of Salmonella spp. in a slaughterhouse in southern Brazil, while Kich et al [ 56 ] reported a frequency of 24%, Cê [ 57 ] 1.11%, and Corbellini et al [ 33 ] 11.5% in the same region.…”
Section: Discussionmentioning
confidence: 99%
“…Cê [ 57 ] analyzed 90 carcasses after final washing and obtained a mean of 1.58 log CFU/cm 2 for Enterobacteriaceae and 3.92 log CFU/cm 2 for mesophilic aerobic counts. Meanwhile, Paim [ 55 ] found results that ranged from −0.8 to 0.46 log CFU/cm 2 for Enterobacteriaceae and 1.43 to 2.48 log CFU/cm 2 for mesophilic aerobic counts.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the monitoring programs of Salmonella in carcasses cannot be discontinued in auto-control programs and official audits, even in slaughterhouses with a good hygienic process. Another important aspect to be considered is the delivery of slaughter batches with high number of Salmonella carrier pigs or the presence of high shedders among the slaughtered pigs, since these factors have been pointed out as leading to enhancement of carcass contamination probability (Duggan et al 2010, Silva et al 2012, Kerouanton et al 2019, Paim et al 2019. In this case, other approaches targeted to the preharvest stage are needed, in order to diminish the pressure in the slaughtering process represented by a high number of Salmonella carrier pigs.…”
Section: Discussionmentioning
confidence: 99%
“…This fact reflects the multiple sources of Salmonella, which includes, associated or not, carrier animals, contaminated feed and environment (Funk & Gebreyes 2004, Kich et al 2005. Still, S. Typhimurium is often reported as the most prevalent serovar in pig and pork (Kich et al 2011, Silva et al 2012, Campos et al 2019, Paim et al 2019). Moreover, this serovar is also frequently reported in human cases and outbreaks associated with pork consumption (Campos et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, it is also possible to observe that S. Typhimurium has been isolated from the intestinal content of pigs, carcasses and surrounding pig environment, which can represent risk of contamination in all meat production processes (ALMEIDA et al, 2016a;PAIM et al, 2019). According to the Brazilian Association of Animal Protein (ABPA), Brazil has been ranked as the fourth largest producer of pig meat, surpassed only by China, EU and the United States, producing 3,983 thousand tons of pig meat and exporting 750 thousand tons in 2019 (ABPA, 2020).…”
Section: Salmonella Typhimuriummentioning
confidence: 99%